Prevalência de tuberculose infecção entre profissionais que trabalham em hospital municipal de emergência em Fortaleza-Ceará - Vasconcelos, Helaine Cristina Alves (2015)
Professionals who provide health care assistance are a risk population for tuberculosis (TB) infection. The tuberculin skin test (TST) plays an important role in the epidemiological control of the disease by identifying individuals at higher risk of developing it. Cross-sectional study investigated the occurrence of TB infection among professionals working in Institute Dr. José Frota (IJF) between the months of October and December 2014 and the level of knowledge that they had about tuberculosis. Sectors of the hospital classified by the occupational health service for the presence or absence of biological risk were grouped for the presence or absence of risk of occupational exposure to M. tuberculosis and soon after, randomly selected from each risk group. Applied a semi-structured questionnaire and the TST. We evaluated 220 professionals, of whom 151 (68.6%) of health care sectors and 69 (31.4%) of administrative area. There was a predominance of female professionals (80.9%) of the median age of 45 years old, who live in the capital (54.1%), with family (90.5%), who have a spouse (72.7%), of average education level (46.9%) and who have never smoked (77.7%) or ingested alcoholic beverages (56.8%). The prevalence of TB infection, evaluated on two occasions, was 47.3% and the presence of the booster effect was identified in 8% of health professionals working in hazardous sectors, among them 3 (1.4%) were nurses, 3 (1.4%) were nursing technician and 1 (0.5%) was a psychologist. The sectors classified as at the highest risk of occupational exposure by M. tuberculosis were the ones with the biggest number of positive results and they were the following the Surgery Center (n = 18; 8.2%), the Emergency (n = 12; 5.5%) and the Traumatology (n = 11; 5%). Among those sectors which were classified as without risk, like the Library and Auditorium (n = 3, 1.4%), the professional testing was positive. The same happened to the testing in the Central Warehouse, Legal Advice and Personnel Services. All these sectors accounted for 2 infected individuals in each. The nursing area was the most affected by positive values: 28 (12.7%) were the nursing technicians, 23 (10.4%) the nursing assistants and 8 (3.6%) nurses. Their test diameters varied from 10mm to 25mm. The analysis of the sociodemographic factors showed that presence of TB infection was significantly associated with schooling (p = 0.017), individual income (p = 0.028) and level of the professional category (p = 0.028). The evaluation of knowledge about TB, revealed that only 7 (3.2%) professionals, working in the Emergency have enough knowledge about it. The topics having the greatest number of right answers was the one addressed on general characteristics of TB infection and transmission. It can be concluded that the prevalence of TB infection in the professionals working in the IJF was considered high and the knowledge that they have about tuberculosis was found to be unsatisfactory